Effect of NK cell receptor genetic variation on allogeneic stem cell transplantation outcome and in vitro NK cell cytotoxicity - Nihtilä, Julia; Penna, Leena; Salmenniemi, Urpu; Itälä-Remes, Maija; Crossland, Rachel E.; Gallardo, David; Bogunia-Kubik, Katarzyna; Lacina, Piotr; Bieniaszewska, Maria; Giebel, Sebastian; Karjalainen, Katariina; Jahan, Farhana; et al. (Springer Science and Business Media LLC, 2025)
Natural killer (NK) cells recognize and may kill malignant cells via their cell surface receptors. Killer cell immunoglobulin-like receptor (KIR) genotypes of donors have been reported to adjust the risk of relapse after allogeneic stem cell transplantation (HSCT), particularly in patients with acute myeloid leukemia. To test whether non-KIR NK cell receptors have a similar effect, we screened 1,638 genetic polymorphisms in 21 non-KIR NK cell receptor genes for their associations with relapse and graft-versus-host disease (GVHD) after HSCT in 1,491 HSCT donors (from Finland, the UK, Spain, and Poland), divided into a discovery and replication cohort. Eleven polymorphisms regulating or located in CD226, CD244, FCGR3A, KLRD1, NCR3, and PVRIG were associated with the risks for relapse and GVHD. These associations could not be confirmed in the replication cohort. Blood donor NK cells carrying alleles showing genetic protection for relapse had a higher in vitro NK cell killing activity than non-carriers whereas those with alleles genetically protective for GVHD had lower cytotoxicity, potentially indicating functional effects. Taken together, these results show no robust effects of genetic variation in the tested non-KIR NK cell receptors on the outcome of HSCT.